Reactivation Mycobacterium Tuberculosis Presenting as Empyema Necessitans 55 Years Following Thoracoplasty - McNulty, Nancy J. (Radiol Case Rep, 2015)
We describe the case of a 79-year-old man who presented with an enlarging mass on his chest wall. He had a history of thoracoplasty performed 55 years ago for treatment of pulmonary tuberculosis. The mass was subsequently proven to be the result of empyema neccesitans caused by reactivation tuberculosis. Empyema neccesitans is a well described entity in which an empyema spontaneously decompresses by dissecting into the chest wall and extrathoracic soft tissues. This can occur following necrotizing pneumonia, including pyogenic or tuberculus, or pulmonary abscess. Complications from collapse therapy for tuberculosis can be encountered decades following the surgery, however, empyema necessitans due to reactivation tuberculosis is rare. This case affords the opportunity to review the goals, techniques, and radiologic appearance of thoracoplasty.